2020
DOI: 10.1177/1521025120921347
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Campus Recreation Facility Use and Retention for First-Time Undergraduate Students

Abstract: This study examines the relationship between campus recreation facility access and first-year retention of full-time, first-time undergraduate students at a public university for 2014–2015 through 2016–2017. Authors examine differences between facility users and nonusers by pairing facility swipe card data with student records. Statistical analysis includes logistic regression and matching approaches, controlling for student demographics, academic preparedness, academic goals, family characteristics, and vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
(146 reference statements)
0
16
0
Order By: Relevance
“…The modeling approach used in this study follows the approach used by Zegre et al (2020). This study uses both logit and ordinary least squares regression-depending on outcome variable-to assess relationships between academic outcomes and participation definitions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The modeling approach used in this study follows the approach used by Zegre et al (2020). This study uses both logit and ordinary least squares regression-depending on outcome variable-to assess relationships between academic outcomes and participation definitions.…”
Section: Methodsmentioning
confidence: 99%
“…Any relationship between facility use and academic outcomes for the average student may differ from the relationships between use and outcomes for students with different characteristics. Thus, we also produced estimates between user definitions for student subsamples, maintaining the same regression model used for all students (Zegre et al, 2020). Subsample groups were broadly created to maintain a large enough sample for statistical analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Student retention has been a major concern for postsecondary institutions attracting attention from educators, policy makers, and academics (Aljohani, 2016). Scholars have found that participation in intramural sport contributes to academic success, student persistence, and retention in postsecondary institutions (Forrester, 2015;Kampf & Teske, 2013;Mayers et al, 2017;Zegre et al, 2020). For example, Kulp et al (2019) found that first year students who participate in extracurricular activities (e.g., intramural sport) experience greater academic success and higher retention rates.…”
Section: Campus Recreation Program Satisfaction and Student Retentionmentioning
confidence: 99%
“…Notably, previous research suggests that participation in intramurals contributes to improved health and physical fitness, greater self-confidence, and improved stress management among students (e.g., Artinger et al, 2006;Forrester, 2015;Huesman et al, 2009). Participation in intramurals has also been linked to increased student satisfaction (e.g., Miller, 2011) retention (e.g., Forrester et al, 2018;McElveen & Rossow, 2014), and grade point average (e.g., Vasold et al, 2021;Zegre et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…a greater sense of belonging within the campus community (e.g., Forrester, 2015;Sanderson et al, 2018;Zegre et al, 2020). While the benefits of collegiate recreation have been promoted for college students generally, few studies have centered on social and academic outcomes for Black undergraduate students, especially those attending historically White colleges and universities (HWCUs).…”
mentioning
confidence: 99%